Telomerase reverse transcriptase promoter mutation- and O6-methylguanine DNA methyltransferase promoter methylation-mediated sensitivity to temozolomide in isocitrate dehydrogenase-wild-type glioblastoma: is there a link? - Gramatzki, Dorothee; Felsberg, Jörg; Hentschel, Bettina; Wolter, Marietta; Schackert, Gabriele; Westphal, Manfred; Regli, Luca; Thon, Niklas; Tatagiba, Marcos; Wick, Wolfgang; Schlegel, Uwe; Krex, Dietmar; et al. (European journal of cancer, 2021)
Aim of the study - Benefit from temozolomide (TMZ) chemotherapy in the treatment of isocitrate dehydrogenase (IDH)-wild-type glioblastoma is essentially limited to patients with O6-methylguanine DNA methyltransferase (MGMT) promoter-methylated tumours. Recent studies suggested that telomerase reverse transcriptase (TERT) promoter hotspot mutations may have an impact on the prognostic role of the MGMT status in patients with glioblastoma. - Methods - MGMT promoter methylation and TERT promoter mutation status were retrospectively assessed in a prospective cohort of patients with IDH-wild-type glioblastoma of the German Glioma Network (GGN) (n = 298) and an independent retrospective cohort from Düsseldorf, Germany, and Zurich, Switzerland (n = 302). - Results - In the GGN cohort, but not in the Düsseldorf/Zurich cohort, TERT promoter mutation was moderately associated with inferior outcomes in patients with MGMT promoter-unmethylated tumours (hazard ratio 1.74; 95% confidence interval: 1.07-2.82; p = 0.026). TERT promoter mutations were not associated with better outcomes in patients with MGMT promoter-methylated tumours in either cohort. The two different TERT promoter hotspot mutations (C228T and C250T) were not linked to distinct outcomes. - Conclusions - Analysis of two independent cohorts of patients with glioblastoma did not confirm previous data, suggesting that TERT promoter mutations confer an enhanced benefit from TMZ in patients with MGMT promoter-methylated glioblastoma. Thus, diagnostic testing for TERT promoter mutations may not be required for prediction of TMZ sensitivity in patients with IDH-wild-type glioblastoma.